1960
DOI: 10.1182/blood.v16.4.1371.1371
|View full text |Cite
|
Sign up to set email alerts
|

Nonspherocytic Congenital Hemolytic Anemia

Abstract: 1. The clinical and hematological features of seven cases of nonspherocytic congenital hemolytic anemia occurring in four different families are presented, together with family studies. Four cases resemble Selwyn and Dacie’s Type I and three cases their Type II. Cases in the literature similar to our cases are reviewed. 2. The Type I cases showed the following features: normocytic or slightly macrocytic anemia with mild hypochromia and some stippling; a decreased or normal osmotic fragility of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

1962
1962
1993
1993

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Noti-Spherocytic Congenital Huemolytic Anaemia, Type I Three subjects from two families with this disorder were studied. Full clinical and haematological data of one subject have been published elsewhere (Case I , de Gruchy et al, 1960), as have results of red-cell phosphate analysis (Robinson et al, 1961). Cases z and 3 are niece and aunt; their haematological and red-cell phosphate values are summarized in Table VI.…”
Section: Normat Suhjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noti-Spherocytic Congenital Huemolytic Anaemia, Type I Three subjects from two families with this disorder were studied. Full clinical and haematological data of one subject have been published elsewhere (Case I , de Gruchy et al, 1960), as have results of red-cell phosphate analysis (Robinson et al, 1961). Cases z and 3 are niece and aunt; their haematological and red-cell phosphate values are summarized in Table VI.…”
Section: Normat Suhjectsmentioning
confidence: 99%
“…
THE non-spherocytic congenital haemolytic anaemias were classified on haematological grounds by Selwyn and Dacie (1954) into two main types-Type I and Type 11. It now seems that Type I cases probably form a heterogeneous group while the Type I1 cases are probably a homogeneous group (de Gruchy, Santamaria, Parsons and Crawford, 1960). Robinson, Loder and de Gruchy (1961) presented evidence of impairment of cell metabolism in both Type I and Type I1 cases and suggested that in Type I1 cases there was an enzymatic defect in glycolysis beyond the stage of z,3-diphosphoglycerate (t,3-DPG) synthesis.
…”
mentioning
confidence: 99%
“…Moreover, Brunetti and coworkers [5] found in their cases a decreased concentration of pentoses in the erythrocytes. Busch [7] described in one case an increased level of GSSG in the red cells and a reduction in the content of NAD and NADH, the last recently confirmed by De Gruchy and coworkers [17].…”
Section: Discussionmentioning
confidence: 70%
“…In this connection it is interesting to note that also in at least some of Dacie's type I1 patients, there seems to be a deficient ATP production (18,20), the cause of which is not known.…”
Section: Discussionmentioning
confidence: 98%